2011
DOI: 10.1021/ol2013395
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Aerobic Oxidative Intramolecular Alkene C–H Amination Leading to N-Heterocycles

Abstract: A copper-catalyzed aerobic oxidative intramolecular alkene C-H amination has been developed using readily available substituted 3-benzylidene-2-pyridin-2-ylmethyl-2,3-dihydro-isoindol-1-ones as the starting materials, and the corresponding N-heterocycles were obtained in good to excellent yields. This method should provide a new and useful strategy for constructing N-heterocycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(31 citation statements)
references
References 84 publications
(25 reference statements)
0
30
0
1
Order By: Relevance
“…102 Specifically, pyridyl substituted 3-methyleneisoindolin-1-ones were treated with catalytic copper(II) trifluoroacetate under air to afford the polycyclic N -heterocycles in good yield (Scheme 50). Limitations to the method include little allowance for structural changes in the substrate and the requirement of several equivalents of pivalic acid.…”
Section: Reactions Of Hydrocarbonsmentioning
confidence: 99%
“…102 Specifically, pyridyl substituted 3-methyleneisoindolin-1-ones were treated with catalytic copper(II) trifluoroacetate under air to afford the polycyclic N -heterocycles in good yield (Scheme 50). Limitations to the method include little allowance for structural changes in the substrate and the requirement of several equivalents of pivalic acid.…”
Section: Reactions Of Hydrocarbonsmentioning
confidence: 99%
“…Fu and co-workers have developed a similar strategy for the intramolecular oxidative amination of vinylic C À H bonds. [97] By treating substituted 3-benzylidene-2-pyridin-2ylmethyl-2,3-dihydro-isoindol-1-ones with 20 mol % Cu-(O 2 CCF 3 ) 2 donating groups led to slightly higher yields than those containing electron-withdrawing substituents, and the reaction was tolerant of C-Cl/Br bonds.…”
Section: Oxidative Annulation Reactionsmentioning
confidence: 99%
“…The corresponding N-heterocycles 1,4-dihydropyrazine derivatives were obtained in good to excellent yields with wide functional group tolerance [183]. Bi, Zhang et al reported a novel Cu(OTf ) 2 -catalyzed preparation of benzoxazine derivatives from readily available N-para-tolylamides in the presence of Selectfluor and water through the intermolecular C-H-activated dehydrogenative cross-coupling reaction (Scheme 8.111).…”
Section: Copper-catalyzed Synthesis Of 14-dihydropyrazine Derivativesmentioning
confidence: 99%